Energy Goods Demand in Tabalong Regency: Almost-Ideal Demand System Approach - Murjani, Ahmadi (Jurnal Bina Praja, 2017)
The declining trend of Tabalong Regency’s economic growth in recent years adversely affected the poverty rate. Further, the recent energy subsidy policy applied by the Indonesian Government has pushed the subsidy’s budget down for some energy goods. Therefore, there should be an awareness regarding the current energy policy and the impact on the poverty particularly in Tabalong Regency. This paper investigates the demand system for the three main energy goods; premium fuel, electricity, and Liquid Petroleum Gas (LPG) in Tabalong Regency of the South Kalimantan Province. Although the same method was previously used on the different topics, this paper uniquely utilizes the combined Linear Approximation and Quadratic Almost-Ideal Demand System on the particular energy policy topic. This paper utilizes the National Social Economics Survey conducted by BPS-Statistics of Tabalong Regency in 2016. The results show that the income elasticity of demand for the top 60% and the bottom 40% of the income groups were positive; however, slight differences could be seen. For the top 60% of the income group, the income elasticities of demand were 0.97, 1.02, and 1.08 for premium fuel, electricity, and LPG respectively. On the other hand, the bottom 40% of the income group had 0.99, 1.07, and 0.91 of income elasticity of demand for premium, electricity, and LPG. The price elasticity of demand for both income groups had negative signs, which is agreeing with the theoretical demand function. These results indicate that the current energy policy should continue with securing the poor households from the possible effect.